Modification of Eye–Head Coordination With High Frequency Random Noise Stimulation - Maeda, Yusuke; Suzuki, Makoto; Iso, Naoki; Okabe, Takuhiro; Cho, Kilchoon; Wang, Yin-Jung (Frontiers in Human Neuroscience, 2020)
The vestibulo-ocular reflex (VOR) plays an important role in controlling gaze at a visual target. Although patients with vestibular hypofunction aim to improve their VOR function, some retain dysfunction for a long time. Previous studies explored the effects of direct current stimulation on vestibular function; however, the effects of random noise stimulation on eye-head coordination have not previously been tested. Therefore, we aimed to clarify the effects of high frequency noisy vestibular stimulation (HF-nVS) on eye-head coordination related to VOR function. Thirteen healthy young adult participants with no serious disease took part in our study. The current intensity and density used were 0.4 mA and 0.2 mA/cm2, respectively, with random noise frequency of 100–640 Hz. The electrodes were located on both mastoid processes. The stimulus duration and fade in/out duration were 600 s and 10 s, respectively. Subjects oscillated their head horizontally, gazing at the fixation point, at 1 Hz (0.5 cycles/s) for 30 repetitions. Coordination of eye-head movements was measured by eye-tracking and a motion capture system. Peak-to-peak angles for eye and head movement, and deviation of the visual line from the fixation target revealed no significant differences between HF-nVS and sham. Lag time between eye and head movement with HF-nVS post-stimulation was significantly shorter than that of sham. We found that HF-nVS can reduce the lag time between eye and head movement and improve coordination, contributing to a clear retinal image. This technique could be applied as a form of VOR training for patients with vestibular hypofunction.